ANALYSIS DICTION AND ANAPHORA LANGUAGE STYLE IN UNILEVER INDONESIA PRODUCTS ADVERTISEMENT ON TELEVISION - Nia Tenia; Rahmat Saripudin (PROJECT (Professional Journal of English Education), 2019)
The purpose of this study are (1) Describe the diction or choice of words in unilever product advertising. (2) Describe the anaphoric language style in unilever product advertising. (3) Describe the function of the sentence in unilever product advertising. Techniques used to collect data in this study is by library techniques, techniques refer, and method of record. Library technique is an attempt to find written or oral data sources that are documentation. Techniques refer to the technique of providing data with the use of language, while the technique of note is advanced techniques refer to the recording of both the written and oral advertisement of unilever products on television. The next step of the data is classified according to the issues discussed about word choice / diction, anaphoral language style, and sentence function in unilever product advertisement. Based on the analysis of diction, anaphora language style, and sentence function on unilever product advertisement on television. The findings derived in the form of dictionary peculiarities are indicated by the use of appropriate and varied expressions and symbols, the use of various terms from foreign languages, and various expressions deliberately exaggerated to reinforce meaning.Keywords: Diction, anaphoric language style, sentence function, unilever product advertisement.